Enhancing Pediatric TB Treatment Compliance: Marketing Strategies for Medication Reminder Devices - Putri, Prahardian; Mulyadi; Meliana; Yomi; Khairunnisa (Yayasan Rumah Ilmu Professor, 2025)
This research focuses on developing a marketing strategy for a medication reminder device (Alarm Obat) to improve medication adherence among children with tuberculosis (TB) in Indonesia. Tuberculosis remains a significant public health challenge, especially in pediatric populations, where adherence to long-term treatment regimens is critical for successful outcomes. The study explores how Alarm Obat, a device designed to remind children to take their medication on time, can help increase adherence and reduce treatment failures. The research also highlights the potential for this product to be integrated into healthcare programs, focusing on partnerships with healthcare institutions and digital marketing strategies. By targeting families with children suffering from TB, the research aims to demonstrate the impact of Alarm Obat on improving health outcomes and reducing the risk of drug resistance. The study concludes by emphasizing the importance of awareness campaigns and collaborative efforts to ensure accessibility and adoption of the product across diverse communities in Indonesia.